2018
DOI: 10.1002/hpm.2603
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of health facilities in Nigeria: Implications and options for Universal Health Coverage

Abstract: The distribution of health facilities across Nigeria is nonuniform. As such, a UHC strategy must be responsive to the variation in health facility distribution across the country. Additional investments are needed in some parts of the country to improve access to tertiary health facilities and leverage private sector capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 29 publications
1
59
0
Order By: Relevance
“…The ndings from this study, like the Liu et al study among others, revealed that PPMV shops were numerous in the two states. With fewer health facilities and health posts opening across the country [29] and fewer pharmacies opening up (especially in rural and hard to reach areas) [14], PPMVs have remained the most widespread health structure across the two (2) states; and across Northern and Southern Nigeria [18]. However, the study found a greater concentration of shops in the Northern state of Kaduna and especially in the urban areas; this is a slight deviation from the norm in many studies that PPMVs are mainly located in the rural and hard to reach areas [16,22,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ndings from this study, like the Liu et al study among others, revealed that PPMV shops were numerous in the two states. With fewer health facilities and health posts opening across the country [29] and fewer pharmacies opening up (especially in rural and hard to reach areas) [14], PPMVs have remained the most widespread health structure across the two (2) states; and across Northern and Southern Nigeria [18]. However, the study found a greater concentration of shops in the Northern state of Kaduna and especially in the urban areas; this is a slight deviation from the norm in many studies that PPMVs are mainly located in the rural and hard to reach areas [16,22,30].…”
Section: Discussionmentioning
confidence: 99%
“…One of the domains of access listed in the UHC includes physical access to health services; this physical accessibility is dependent on the proximity of health facilities to potential clients [31]. In a recent study where the distribution of health facilities across Nigeria was documented, primary health facilities, more than other facilities were most prominent across the country (ranging 15.5 and 18.4 per 100,000 population in Southern and Northern states respectively) [29]. The ndings from our study showed that the distribution of PPMV shops in these regions more than doubled that of the most populous health facilities; ranking 32 and 46 per 100,000 respectively in Southern state of Lagos and Northern state of Kaduna; this corroborates the ndings of Liu and colleagues that PPMVs may be more accessible than health care facilities in many places across Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Our results contribute to the literature by finding consistent results through a more comprehensive analysis of the distribution of health clinics in Nigeria. To our knowledge, our paper is the first to evaluate the correlation between the quantity and the quality of existent clinics in Nigeria in a comprehensive way [31]. …”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, the health care system is made up of three levels: primary, secondary, and tertiary, depending on the level of services required by patients. The provision of primary health care (PHC) services is the responsibility of the local government, while the secondary healthcare services are under the state government, and the tertiary healthcare services under the federal government [31]. PHC clinics are the first point of contact for patients, who are then referred to the higher-level secondary and tertiary facilities depending on the level of treatment required [32].…”
Section: Introductionmentioning
confidence: 99%
“…A 2016 analysis of the Nigerian Master Health Facility List by Makinde et al . reported that primary‐level health facilities account for 88% of all facilities in Nigeria.…”
Section: Discussionmentioning
confidence: 99%